GSK3β-mediated Keap1-independent regulation of Nrf2 antioxidant response: A molecular rheostat of acute kidney injury to chronic kidney disease transition - Lu, Minglei (Redox Biol, 2019)
Transition of acute kidney injury (AKI) to chronic kidney disease (CKD) represents an important cause of kidney failure. However, how AKI is transformed into CKD remains elusive. Following folic acid injury, mice developed AKI with ensuing CKD transition, featured by variable degrees of interstitial fibrosis and tubular cell atrophy and growth arrest. This lingering injury of renal tubules was associated with sustained oxidative stress that was concomitant with an impaired Nrf2 antioxidant defense, marked by mitigated Nrf2 nuclear accumulation and blunted induction of its target antioxidant enzymes, like heme oxygenase (HO)-1. Activation of the canonical Keap1/Nrf2 signaling, nevertheless, seems intact during CKD transition because Nrf2 in injured tubules remained activated and elevated in cytoplasm. Moreover, oxidative thiol modification and activation of Keap1, the cytoplasmic repressor of Nrf2, was barely associated with CKD transition. In contrast, glycogen synthase kinase (GSK)3β, a key modulator of the Keap1-independent Nrf2 regulation, was persistently overexpressed and hyperactive in injured tubules. Likewise, in patients who developed CKD following AKI due to diverse etiologies, like volume depletion and exposure to radiocontrast agents or aristolochic acid, sustained GSK3β overexpression was evident in renal tubules and coincided with oxidative damages, impaired Nrf2 nuclear accumulation and mitigated induction of antioxidant gene expression. Mechanistically, the Nrf2 response against oxidative insult was sabotaged in renal tubular cells expressing a constitutively active mutant of GSK3β, but reinforced by ectopic expression of dominant negative GSK3β in a Keap1-independent manner. In vivo in folic acid-injured mice, targeting GSK3β in renal tubules via conditional knockout or by weekly microdose lithium treatment reinstated Nrf2 antioxidant response in the kidney and hindered AKI to CKD transition. Ergo, our findings suggest that GSK3β-mediated Keap1-independent regulation of Nrf2 may serve as an actionable therapeutic target for modifying the long-term sequelae of AKI.